2017
DOI: 10.1002/ajmg.a.38215
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous variant in C21orf2 in a case of Jeune syndrome with severe thoracic involvement: Extending the phenotypic spectrum

Abstract: We previously reported exome sequencing in a short-rib thoracic dystrophy (SRTD) cohort, in whom recessive mutations were identified in SRTD-associated genes in 10 of 11 cases. A heterozygous stop mutation in the known SRTD gene WDR60 was identified in the remaining case; no novel candidate gene/s were suggested by homozygous/compound heterozygous analysis. This case was thus considered unsolved. Re-analysis following an analysis pipeline update identified a homozygous mutation in C21orf2 (c.218G > C; p.Arg73P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…CME was not reported previously and prior reports documented more severe retinal degeneration than was observed in the present study. C21orf2 mutations have also been reported in patients with syndromic forms of retinal degeneration, including Jeune syndrome [ 24 ] and axial spondylometaphyseal dysplasia [ 25 , 26 ]. Homozygous mutations in the CACNA2D4 gene have been associated with autosomal recessive cone rod dystrophy [ 27 , 28 ] and nonprogressive inner retinal cone system dysfunction [ 29 ], but carriers with only one mutation in the CACNA2D4 gene had no symptoms [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CME was not reported previously and prior reports documented more severe retinal degeneration than was observed in the present study. C21orf2 mutations have also been reported in patients with syndromic forms of retinal degeneration, including Jeune syndrome [ 24 ] and axial spondylometaphyseal dysplasia [ 25 , 26 ]. Homozygous mutations in the CACNA2D4 gene have been associated with autosomal recessive cone rod dystrophy [ 27 , 28 ] and nonprogressive inner retinal cone system dysfunction [ 29 ], but carriers with only one mutation in the CACNA2D4 gene had no symptoms [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to kizuna, C21orf2 encodes a protein that localizes to photoreceptor-connecting cilia [ 22 ]. Although many ciliopathies affect organ systems, in addition to causing retinal degeneration [ 23 , 24 , 25 ], many affect the retina exclusively, such as in certain forms of RP or Leber congenital amaurosis [ 30 ]. All three patients in the current study had ocular manifestations including nyctalopia, mid-peripheral visual field loss, and retinal pigmentary changes, without extraocular findings suggestive of a syndromic disease, although II:2 developed mild hearing loss by age 52, and prior studies in KIZ –related RP reported moderate hearing loss in one patient by age 50 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications of SRPS and ATD cases from the ISDR have included 22 additional families with mutations in nine ciliary genes ( DYNC2H1, WDR34, IFT52, ICK, INTU, IFT81, DYNC2LI1, IFT43 , and WDR35 ), including six genes not represented among the current set of families (Duran, et al., ; Huber et al., ; Taylor et al., ; Taylor et al., ; Toriyama et al., ; Zhang et al., ). Mutations have also been reported in families in this spectrum of disease in six additional genes, C21ORF2 (McInerney‐Leo et al., ; Wheway et al., ), TCTEX1D2 (Gholkar et al., ), IFT172 (Halbritter et al., ), KIAA0586 (Alby et al., ), CEP120 (Shaheen et al., ), or IFT122 (Walczak‐Sztulpa et al., ), bringing the number of known skeletal ciliopathy genes to twenty six. A model of the ciliary complexes showing the components mutated in the disorders is shown in Figure .…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, mutations in only a subset of the genes encoding IFT‐B complex members, IFT80 (Cavalcanti et al., ), IFT172 (Halbritter et al., ), IFT52 (Zhang et al., ), and IFT81 (Duran, et al., ), have been identified among the skeletal ciliopathies. In addition, mutations in two genes ( EVC (Ruiz‐Perez et al., ), EVC2 (Galdzicka et al., )) that encode basal body proteins, the NEK1 kinase gene (Thiel et al., ) and the gene encoding its interacting protein C21ORF2 (McInerney‐Leo et al., ; Wheway et al., ), the ICK MAP‐like kinase gene (Taylor et al., ), the INTU planar cell polarity (PCP) gene (Toriyama et al., ), the KIAA0586 (Alby et al., ) centrosomal protein gene, and the CEP120 core centriolar protein gene (Shaheen et al., ) have also been reported. Mutations in several of these genes, including the latter five genes, are rare causes of skeletal ciliopathies, each having been observed in only one or a few families.…”
Section: Introductionmentioning
confidence: 99%
“…Variable extraskeletal manifestations include structural and functional abnormalities of the brain, retina, genitalia, kidney, and liver 4 . So far, mutations in 25 genes, coding for cilia or basal body structural proteins and intraflagellar transport proteins, have been identified in association with skeletal ciliopathies and the number of genes causing these conditions keeps growing 2 , 4 9 .…”
Section: Introductionmentioning
confidence: 99%